Barriers to democracy the other side of social capital in Palestine and the Arab world - Jamal, Amaney A. 1970- (Princeton University Press, 2007)
Investigates the role of civic associations in promoting democratic attitudes and behavioral patterns in contexts that are less than democratic. This work argues that, in state-centralized environments, associations can just as easily promote civic qualities vital to authoritarian citizenship - such as support for the regime in power